Lesena montažna skeletna gradnja - Zalokar-Miklič, Romeo (Les (Ljubljana), 2002)
Wooden skeleton construction is one of the prefabricated systems that are used for building single family houses. Abroad is known as industrial or tradesman`s prefabricated system. Most of investors usually decide to build their home in tradesman`s manner. In Slovenia wooden skeleton system stil do not have right value on single family building market. In this article is presented system and their characteristics.
Keywords: montažna gradnja; lesene konstrukcije